Pemanfaatan Energi Terbarukan: Pemasangan Lampu Penerangan Jalan Berbasis Panel Surya Di Jorong Siamang Bunyi Dan Koto Serikat, Kabupaten Lima Puluh Kota - Azmen Kahar; Afriyus Missiyona; Gita Lista; Gilang Pratama; Silvia Silvia (CV. ITTC INDONESIA, 2026)
The limited street lighting infrastructure in rural areas is one of the most common problems faced by communities, including those in Jorong Siamang Bunyi and Koto Serikat, Lima Puluh Kota Regency, West Sumatra. Dark roads at night not only reduce residents' comfort in carrying out daily activities, but also increase the risk of traffic accidents and security disturbances. This Community Service Program (KKN) of UNP Nagari Kubang aims to address these issues through the installation of solar panel-based public street lighting (PJU) as a sustainable renewable energy solution. The implementation method includes site surveys, community needs assessment, coordination with the nagari government, procurement of equipment and materials, as well as direct installation and system testing in the field. The results show that the installation of solar-powered lights at strategic points in both jorong successfully improved lighting quality significantly. The community responded positively to this program, as the lights operate automatically, require no connection to the state electricity grid (PLN), and incur no monthly operational costs. This program also provided residents with a new understanding of the importance of utilizing renewable energy in everyday life. It is hoped that the success of this program can serve as a reference for future generations in adopting environmentally friendly technology to meet their lighting needs.